The Effectiveness of Donald Super Career Counseling in Increasing Student Self Efficacy and Career Commitment - Asfarina Mutiara; Budi Astuti (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2021)
The study aims to determine the effectiveness of Donald Super's career counseling in increasing student self-efficacy and career commitment. This experimental research involved 20 guidance and counseling department students in the Special Region of Yogyakarta, Indonesia, recruited using purposive sampling technique. The subjects were divided into two groups. Self-efficacy and career commitment scales were deployed to collect the data. The collected data were analyzed using Wilcoxon test. The results of the study show that Donald Super's career counseling wasÂ  effective in increasing self-efficacy and career commitment of guidance and counseling students. The results of this study can be used as a reference by counselors in higher education to increase self-efficacy and career commitment of students using Donald Super's career counseling.